The influence of a mindfulness-based intervention on job satisfaction and work-related stress and anxiety. Issue 3 (27th May 2017) - Wongtongkam, Nualnong; Krivokapic-Skoko, Branka; Duncan, Roderick; Bellio, Mariagrazia
Abstract: Workplace mindfulness is a recognised tool for enhancing health and well-being of university staff and may result in better task performance and satisfaction in the workplace. The study examined the beneficial effects of mindfulness meditation on job satisfaction, mindful awareness and anxiety levels in university personnel. Mixed methods with a quasi-experiment and in-depth interviews were used. Fifteen participants engaged in a mindfulness meditation approach and five volunteers were interviewed. The findings showed a significant increase in awareness, with staying focused ( t (14) = –3.09, p = .00), noticing feelings of physical tension ( t (14) = –4.00, p = .00), being aware of running automatically ( t (14) = –3.55, p = .00) and not being preoccupied with the future or the past ( t (14) = –2.69, p = .01), respectively. Mindfulness was also effective in reducing sleep disturbance. Qualitative results demonstrated the mindfulness approach contributed to calmness and relaxation, and increased ability to handle difficult matters in the workplace. Apart from helping participants to better manage emotions, the mindfulness intervention could promote better relationships towards family members and reduce blood pressure to normal levels. Therefore, mindfulness meditation should be promoted across academic settings to enhance job performance and satisfaction and reduce work-related stress.